Empowering Students with Digital Religious Literacy: The Contribution of Islamic Education Teachers - Giovany, Ananda; Rahman, Kholilur; Wahyono, Imam (STKIP PGRI SITUBONDO, 2024)
The purpose of this study is to examine the role of Islamic Religious Education Teachers (PAI) in improving the religious digital literacy skills of students at SMAN 1 Glagah Banyuwangi. In this digital era, digital literacy skills are one of the main competencies that must be possessed by every individual, including in the context of religious education. This study uses a qualitative approach with a case study type of research. Data collection techniques include in-depth interviews with PAI teachers, students, principals, and parents of students, direct observation in classrooms and school environments, and analysis of documentation such as curriculum, lesson plans, and digital teaching materials. The data analysis technique is carried out through data triangulation, which aims to ensure the validity and reliability of the findings by comparing data from various sources to get a comprehensive picture. The results of the study show that PAI teachers at SMAN 1 Glagah Banyuwangi play a crucial role in improving students' religious digital literacy through various strategies, such as the provision of relevant materials, the use of technology in the learning process, the development of an inclusive curriculum, and the provision of adequate resources and references. PAI teachers also face several challenges, including limited resources and the need to constantly update their tech skills. This writing is expected to provide in-depth insights into the best practices and challenges faced by PAI teachers in the digital era.